Keberadaan Simbol dalam Pemujaan Umat Hindu di Bali Perspektif Teologi Hindu - I Ketut Manik Asta Jaya; I Made Wirahadi Kusuma (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Hinduism is an Art religion. In simple terms, art can be defined as the result of a creation or the fruit of human thoughts and feelings that are expressed in form or form, sound and others. Which can give happiness to the heart and life. Therefore, through works of art such as sculptures or others, Hindus pour their beliefs and feelings into Ida Sang Hyang Widhi Wasa. Through this work of art, Hindus concentrate more on worshiping the infinite greatness of God and are more concentrated on worshiping God who is unmanifest, unthinkable and inconceivable by this limited human mind. In order to always have a harmonious relationship between creation and creator, human limitations must be recognized. Based on this, there are two ways to appreciate God, namely: Sagunam (manifested) which is immanent and Nirgunam (unmanifested) which is transcendent. Man realizes that God has power beyond the limits of human strength and the human mind itself. There is nothing that exactly defines God Himself. And for most people it is very difficult to imagine (menuja) such a God, so the Vedas provide two methods of worshiping God, namely Pratika-Upasana or Sagunam-Upasana and Ahamgara-Upasana or Nirgunam-Upasana Starting from this, worship uses good symbols. it is in the form of statues, pictures, offerings and others that are often seen in various rituals of worship of Hindus in general, including the Sagunam-Upasana worship.